A New Era for EJFB - López-Fernández, M. Concepción; Maseda, Amaia (European Journal of Family Business, 2021)
To commemorate the 10th anniversary of the European Journal of Family Business (EJFB), we are pleased to present this issue (volume 11, no.1) that has involved the participation of prominent authors who have made significant contributions to the growth and consolidation of the family business in the field of research and to EJFB over the years. The papers presented in this issue provide an ideal opportunity to present how the field has evolved in recent years, but also to reflect on contemporary challenges in the broad domain of family business. When the journal was launched in 2011, family business research attracted widespread attention from a growing audience due to the relevance of the topic for scholars and practitioners. Family business practitioners (lawyers, accountants, business consultants, family office directors, family philanthropy managers, financial services advisors, management consultants, family therapists and psychologists among others) were key elements in the dawn of the family business (Sharma, Chrisman, & Gersick, 2012). Providing assistance to both family business operators and advisors in understanding family firms was indeed one of the many reasons for the creation of Family Business Review (Lansberg, Perrow, & Rogolsky, 1988) and later for the creation of the Journal of Family Business Strategy (Astrachan & Pieper, 2010). The family firm field is fortunate that many of those who have brought this field forward have focused on ensuring that the field had a good theoretical foundation that facilitated research and allowed the field to progress (Vought, Baker, & Smith, 2008). But it is also true that following the strong tradition of theory-building and testing expected in high-quality business journals (Sharma et al., 2012) has led the practice orientation of the family firm field to change over time (Reay, Pearson, & Dyer, 2013, p.209). The field became mostly research-oriented, relying heavily on quantitative empirical research. We believe that these studies should be complemented by other research approaches that allow for capturing the specific complexity and dynamics unique to family firms (Nordqvist Hall & Melin, 2009). The literature shows diverse examples of how collaboration between professionals and researchers (e.g., Davis et al., 2013) is a successful way to promote more research (Reay et al., 2013, pp. 210). In a business world that is increasingly cognisant of the critical role of evidence-based management, family firm practitioners need to be connected to research while having the potential to serve as a mechanism for transferring research knowledge to implementable practices (Reay et al., 2013). ‘Practitioners can identify the actions and access sources. Researchers must search for the meaning of those actions, their interlinkages, and what the act represents to develop theoretical propositions’ (Strike, 2012, pp. 168). Similarly, more practice-oriented research is also necessary to aid practitioners in advancing their knowledge of family firms from a research perspective. In summary, practitioners and researchers need to work together to enhance the research agenda by learning scientifically from practice and applying ‘the theoretical and empirical research findings back to practice’ (Strike, 2012, pp. 169). This is the gap that EJFB wants to fill in its new era. We consider this issue to be a good example of our vision of the journal. Thus, for example, the paper by Ernesto Poza-Valle (2021) offers a review of the academic research and practitioner best practices literature highlighting how little we still know about the role that ownership control plays in the continuity of founder-controlled and family-controlled firms. Statutory ownership control, psychological ownership and family unity approaches are all considered in an exploration of a future ownership development perspective and approaches that controlling families can take to preserve ownership control. In the same vein, based on the author’s experience with entrepreneurs who built successful businesses, the paper of Miguel Angel Gallo (2021) identifies four elements that are critical to achieving transgenerational continuity in family firms: coexistence, unity, professionalism and prudence. The paper provides guidance to help both scholars and practitioners in the family business field pursue the continuity of the family firm over time. Cristina Cruz, Rachida Justo and Jeanne Roch (2021) expand our knowledge of the intersection between the family and the firm. In particular, they develop a theoretical framework explaining why and how business-owning families engage in impact investing. For a business to be sustainable as a family firm across the years, it is necessary to look at the internal processes that occur within the firm itself and understand the relationship between the family and the business. Where have we come from, where are we now? Gloria Aparicio, Txomin Iturralde, José Carlos Casillas and Encarnación Ramos-Hidalgo (2021) present a bibliometric analysis of family firm research, giving a holistic overview with a bibliometric evaluation of 3,368 articles published from 2010 to 2020 on family firms. The study provides a synthesis and organisation of existing knowledge on family firm research. A practical perspective is presented in the paper of Paco Valera, Neus Feliu and Ivan Lansberg (2021). They use the metaphor of biological DNA to describe generic and specific family business cultures and suggest that Latin family businesses inherited four key cultural DNA building blocks—trust, loyalty, authority and justice—from historical Roman times. Like biological DNA, family businesses are forced to change in order to be fit for the future. They draw upon their firm's 30 years of work consulting with Latin family businesses and present a wide range of supporting cases and stories. Juan Corona (2021) approaches the great issue that affects the vast majority of family firms, successful succession. Through his expertise, the author shares his thoughts about the importance of the successor's preparation, the role of family harmony and the necessity of developing a new generation of leaders. The commentary of Gibb Dyer (2021) describes the trends in the field of family business over the past forty years in terms of theory and practice. Topics such as succession, consulting with family businesses, the effectiveness of family firms, the role of socio-emotional wealth in family firms, heterogeneity in family businesses and the impact of family capital on the business and the family are discussed. The worldwide explosion of interest in family business research has created a knowledge vacuum requiring educators, scholars and practitioners to share their collective wisdom to further the field. Specifically, we would like to encourage family business practitioners to write about their experiences, partner with researchers and academics to systematically study advising and share their work through contributions to EJFB. This collaboration will allow the family business field to further understand the ‘what’ of the intricacies and dynamism of family business captured in descriptive works and explore the ‘how, when and why’ that arise when theory is developed to inform practice. So, long live family business research! Editors in this Issue Dr. M. Concepción López-Fernández, University of Cantabria Dr. Amaia Maseda, University of the Basque Country